The effect of knowledge and role of social security organization on members awareness towards their savings after the retirement / Nadia Azia Omar - Omar, Nadia Azia (Bachelor of Science (Hons) Statistics, 2015)
The purpose of this study is to determine the effect of knowledge and role social security organization on the member’s awareness towards their savings after the retirement for the active members at EPF Kuala Terengganu. The study taken 201 respondents used the simple random sampling technique and collected by administrative distributed questionnaires that have two section, part A and part B. The data was analyzed using the AMOS and SPSS. The Structural Equation Modeling (SEM) approach used to investigate the relevant hypothesis among the constructs. The result shows knowledge and role social security organization have positive effect on the members awareness towards their savings after the retirement